Literature Review: Penerapan Teknologi Informasi dalam Meningkatkan Kualitas Pelayanan Publik - Bambang Suprianto (Jurnal Pemerintahan dan Politik, 2023)
The number of complaints submitted by the public about the poor process of public services provided is a problem that must be immediately addressed by the Government. Along with the current advances in information technology, many institutions or agencies have begun to overhaul work systems in order to improve the quality of service to the public. This research aims to identify the application of information technology in improving the quality of public services. This research uses descriptive qualitative methods and the research sources used are secondary data, namely studies of literature, articles, journals, regulations, and sites on the internet related to this research. Validity data in study using triangulation. This study uses the theory of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. The findings of this study are that the application of information technology in improving the quality of public services has not fully run optimally, this can be seen from the dimensions of physical evidence (tangibles) that have not utilized digitalization in optimizing technology so that it requires space and storage space to store files and documents that are increasingly mounting. reliability in technology-based services, information and communication networks is very dependent on the weather, because if there is heavy rain or thunderstorms, the quality of the network becomes weak and even stops so that the process of administering (managing and processing) data becomes slow and can cause inaccuracies, power responsiveness is still not optimal because the services provided are still slow and require a long time